Narrow genetic base in forest restoration with holm oak (Quercus ilex L.) in Sicily (Annals of forest …, 2007)
In order to empirically assess the eﬀect of actual seed sampling strategy on genetic diversity of holm oak (Quercus ilex) forestations in Sicily, we have analysed the genetic composition of two seedling lots (nursery stock and plantation) and their known natural seed origin stand by means of six nuclear microsatellite loci. Signiﬁcant reduction in genetic diversity and signiﬁcant diﬀerence in genetic composition of the seedling lots compared to the seed origin stand were detected. The female and the total eﬀective number of parents were quantiﬁed by means of maternity assignment of seedlings and temporal changes in allele frequencies. Extremely low eﬀective maternity numbers were estimated (Nf e ≈ 2–4) and estimates accounting for both seed and pollen donors gave also low values (Ne ≈ 35–50). These values can be explained by an inappropriate forestry seed harvest strategy limited to a small number of spatially close trees.